Performance Implications of The Absorptive Capacity of Small Businesses in A Developing Economy - Chukuakadibia Eresia-Eke; Udo Osuigwe (Research Synergy Foundation, 2022)
The role of small businesses in the socioeconomic development of nations has been well established. Despite this, the failure rate of small businesses in developing economies remains high. Much of this stems from poor performance levels on the part of small businesses which is often exacerbated by the continued flux and disruptions in the business environment. Recognising the importance of astute responsiveness to the dynamic business environment, this study investigates whether absorptive capacity can energise small business performance. The study employed the partial least squares structural equation modelling technique and multiple regression analysis to analyse data collected from an effective pool of 685 small business owners/managers. The results affirm that absorptive capacity has a positive though a weak relationship with small business performance. Interestingly, when the absorptive capacity construct was disaggregated, it was insightful to note that not all its components bear statistically significant relationships with small business performance. Specifically, the relationships between small business performance and the component factors of assimilation and exploitation were statistically supported. In contrast, the factors of acquisition and transformation have no statistically significant relationship with small business performance. The finding has important implications for practitioners and researchers as it illuminates specific components of absorptive capacity that deserve higher investments in the quest for improved small business performance. Keywords: Absorptive capacity; Entrepreneurship; Small business; Performance